Pengaruh Kompensasi, Lingkungan Kerja Dan Kepemipinan Terhadap Kepuasan Kerja Guru Pada Sekolah Madrasah Yogyakarta - Candra; Dahri, Nur Wahyunianti; Aqil, Muhammad (SMARTINDO, 2023)
This research was conducted to analyze the influence of compensation, work environment and leadership on teacher job satisfaction at Madrasah Yogyakarta, which aims to manage superior and advanced human resources in facing this era of globalization, one of which is by paying attention to employee satisfaction. the role of human resources is the planner and implementer in the organization's achievement.This research uses quantitative descriptive methods with data analysis techniques using validity tests, reliability tests, multiple linear regression analysis, t tests, f tests and tests carried out manually using the SPSS 22.0 for Windows application. The population in this study were teachers at Madrasah Yogyakarta, while the sample included was 57 samples.The results of the research show that, in the validation test each variable was smaller than the significance of 0.05 (valid), the reliability test value was 0.946, it was greater than 0.60 (reliable), the multiple linear regression analysis value of job satisfaction was 8.344, the compensation value was 0.053, the work environment value was 0.333 , and leadership 0.297, partial t test compensation has no effect, but it does influence the work environment and leadership on job satisfaction, the f test simultaneously has an influence on teacher job satisfaction. The greatest level of influence is based on multiple linear analysis, the highest beta value of the work environment with a valueof 0.333 compared to the values of other independent variables